2022
DOI: 10.5194/acp-22-2553-2022
|View full text |Cite
|
Sign up to set email alerts
|

Urban inland wintertime N<sub>2</sub>O<sub>5</sub> and ClNO<sub>2</sub> influenced by snow-covered ground, air turbulence, and precipitation

Abstract: Abstract. The atmospheric multiphase reaction of dinitrogen pentoxide (N2O5) with chloride-containing aerosol particles produces nitryl chloride (ClNO2), which has been observed across the globe. The photolysis of ClNO2 produces chlorine radicals and nitrogen dioxide (NO2), which alter pollutant fates and air quality. However, the effects of local meteorology on near-surface ClNO2 production are not yet well understood, as most observational and modeling studies focus on periods of clear conditions. During a f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 68 publications
(86 reference statements)
2
16
0
Order By: Relevance
“…The large measurement uncertainties in the snowpack ClNO 2 emission fluxes resulted in a significant range of modeled ClNO 2 (Figure b), indicating that the ClNO 2 simulations were highly sensitive to the snowpack emissions. The important role of snowpack ClNO 2 production in the simulations is consistent with the whole-campaign observations by Kulju et al, who found higher ClNO 2 mole ratios when snow-covered ground was present, which could not be explained by air turbulence, N 2 O 5 , or several other variables, and attributed this finding to the snowpack ClNO 2 flux. The NO 2 level did not have a significant impact on the simulated ground-level ClNO 2 , as shown in Figure S12, since the corresponding model layer was constrained with the measured N 2 O 5 at the field site.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The large measurement uncertainties in the snowpack ClNO 2 emission fluxes resulted in a significant range of modeled ClNO 2 (Figure b), indicating that the ClNO 2 simulations were highly sensitive to the snowpack emissions. The important role of snowpack ClNO 2 production in the simulations is consistent with the whole-campaign observations by Kulju et al, who found higher ClNO 2 mole ratios when snow-covered ground was present, which could not be explained by air turbulence, N 2 O 5 , or several other variables, and attributed this finding to the snowpack ClNO 2 flux. The NO 2 level did not have a significant impact on the simulated ground-level ClNO 2 , as shown in Figure S12, since the corresponding model layer was constrained with the measured N 2 O 5 at the field site.…”
Section: Resultssupporting
confidence: 89%
“…N 2 O 5 and ClNO 2 observations for the full SNACK campaign were previously reported by Kulju et al Over the full campaign, N 2 O 5 mole ratios were not statistically significantly different between the snow-covered and bare ground periods . In contrast, on average over the full campaign, ClNO 2 mole ratios were higher over snow-covered ground compared to bare ground due to snowpack ClNO 2 production . Here, we focus this modeling study on two case studies, the nights of Jan 31 and Jan 30, which were chosen to represent the bare ground and snow cover periods, respectively (Figure ).…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Therefore, at low temperatures, R moves right, namely, N 2 O 5 formation. As a result, N 2 O 5 dissociation (left direction of R ) slows; thus, net N 2 O 5 formation is favorable at low temperatures (right direction of R ), , forming ClNO 2 (R ) that competes with the N 2 O 5 hydrolysis process (R ). This low-temperature process illustrates ClNO 2 formation on Cl-containing spray aerosols along the Arctic coast or in coastal regions in winter.…”
Section: Introductionmentioning
confidence: 99%